The Hidden Majority? Exploring the Neurodiversity in CAMHS Eating Disorder Caseloads - Rachel Lewis; Megan Davies-Kabir (BJPsych Open)
Aims: Emerging research indicates a higher prevalence of Autism Spectrum Disorder (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD) among individuals with eating disorders (EDs) compared with the general population. Understanding this overlap is crucial for service planning, as neurodiversity assessments and tailored interventions require additional clinical resources. This study aimed to quantify the incidence of neurodiversity within a community specialist Child and Adolescent Mental Health Services (CAMHS) ED caseload to better predict workload demands and inform clinician training and treatment adaptations.